2021
DOI: 10.1029/2020ja028601
|View full text |Cite
|
Sign up to set email alerts
|

New Type of Short High‐Frequency VLF Patches (“VLF Birds”) Above 4–5 kHz

Abstract: The main feature of the magnetosphere consists in its filling with a large variety of waves at different frequency scales with different characteristics and of different origins. The natural electromagnetic waves at the audio range of frequencies (3-30 kHz) termed very low frequency (VLF) emissions are typical for the magnetospheric plasma as well. They are whistler mode waves of magnetospheric origin at the frequencies between the ion and electron gyrofrequency, that have propagated through the ionosphere to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 45 publications
4
19
0
Order By: Relevance
“…These numbers show that VLF bursty-patches are not a rare occurrence and are observed quite frequently at KAN, also supporting recent results by Manninen et al (2021). On the other hand, other studies have reported VLF bursty-patches at other ground stations (e.g., Shiokawa et al 2014;Martinez-Calderon et al 2015) but they are only mentioned as few selected cases.…”
Section: General Occurrence Of Vlf Bursty-patchessupporting
confidence: 90%
See 2 more Smart Citations
“…These numbers show that VLF bursty-patches are not a rare occurrence and are observed quite frequently at KAN, also supporting recent results by Manninen et al (2021). On the other hand, other studies have reported VLF bursty-patches at other ground stations (e.g., Shiokawa et al 2014;Martinez-Calderon et al 2015) but they are only mentioned as few selected cases.…”
Section: General Occurrence Of Vlf Bursty-patchessupporting
confidence: 90%
“…This seems to be in agreement with the solar cycle 24 whose minimum was also in 2018, suggesting that VLF bursty-patch generation or propagation are affected by the solar cycle. Previous studies also found that VLF bursty-patches are mostly observed during quiet space weather conditions at times of small negative Dst values (Manninen et al 2021). To understand how solar wind condition affect VLF bursty-patches we need to focus on statistics and their relation to solar wind parameters which are outside of the scope and this paper and will be the subject of a separate study.…”
Section: General Occurrence Of Vlf Bursty-patchesmentioning
confidence: 69%
See 1 more Smart Citation
“…This seems to be in agreement with the solar cycle 24 whose minimum was also in 2018, suggesting that VLF bursty-patch generation or propagation are affected by the solar cycle. Previous studies also found that VLF burstypatches are mostly observed during quiet space weather conditions at times of small negative Dst values (Manninen et al, 2021). To understand how solar wind condition affect VLF bursty-patches we need to focus on statistics and their relation to solar wind parameters which are outside of the scope and this paper and will be the subject of a separate study.…”
Section: General Occurrence Of Vlf Bursty-patchesmentioning
confidence: 99%
“…The approximate timings of observations of these events are indicated by magenta lines at the top of the spectrum. These emissions are characterized by multiple bursts that have spectral features resembling the shape of a cartoon bird seen from the side (e.g., Manninen et al 2017Manninen et al , 2021. Indeed, with a little bit of imagination the VLF bursty-patches from 09:30 to 10:30 UT could even be seen as a peacock.…”
Section: 'Bird' Vlf Bursty-patchesmentioning
confidence: 99%